Farm-Level Risk Factors Associated With Avian Influenza A (H5) and A (H9) Flock-Level Seroprevalence on Commercial Broiler and Layer Chicken Farms in Bangladesh - Gupta, Suman Das; Fournié, Guillaume; Hoque, Md. Ahasanul; Henning, Joerg (Frontiers in Veterinary Science, 2022)
A cross-sectional study was conducted to identify farm-level risk factors associated with avian influenza A H5 and H9 virus exposure on commercial chicken farms in Bangladesh. For broiler farms, both H5 and H9 seropositivity were associated with visits by workers from other commercial chicken farms [odds ratio (OR) for H5 = 15.1, 95% confidence interval (CI): 2.8–80.8; OR for H9 = 50.1, 95% CI: 4.5–552.7], H5 seropositivity was associated with access of backyard ducks (OR = 21.5, 95% CI: 2.3–201.1), and H9 seropositivity with a number of farm employees (OR = 9.4, 95% CI: 1.1–80.6). On layer farms, both H5 and H9 seropositivity were associated with presence of stray dogs (OR for H5 = 3.1, 95% CI: 1.1–9.1; OR for H9 = 4.0, 95% CI: 1.1–15.3), H5 seropositivity with hatcheries supplying chicks (OR = 0.0, 95% CI: 0.0–0.3), vehicles entering farms (OR = 5.8, 95% CI: 1.5–22.4), number of farm employees (OR = 5.8, 95% CI: 1.2–28.2), and burying of dead birds near farms (OR = 4.6, 95% CI: 1.2–17.3); H9 seropositivity with traders supplying feed (OR = 5.9, 95% CI: 1.0–33.9), visits conducted of other commercial poultry farms (OR = 4.7, 95% CI: 1.1–20.6), number of spent layers sold (OR = 24.0, 95% CI: 3.7–155.0), and frequency of replacing chicken droppings (OR = 28.3, 95% CI: 2.8–284.2). Policies addressing these risk factors will increase the effectiveness of prevention and control strategies reducing the risk of avian influenza on commercial chicken farms.